Histological Variation in the Number and Diameter of the Postmortem Human Pancreatic Islets in Relation to Age and Sex: Insight from North East Bangladesh (Journal of Armed Forces Medical College, Bangladesh, 2024)
Background: Disease pattern as well as diagnostic and treatment options may be helped by examining the number and diameter of Islets of human pancreas, as the change with age. It seems that there is a research vacuum in this area and demands more studies, including gross anatomical studies, with data available in Bangladesh.Objective: To find out the histological variations of post mortem human pancreas in relation to age and sex of north east region of Bangladesh.Methods: Fifty human postmortem pancreases were selected. The inclusion criteria was dead bodies autopsied within 36 hours of death; while considerable signs of decomposition, decomposed dead body, dead body autopsied exceeds 36 hours after death, presence of gross pancreatic disease and poisoning cases were excluded. The obtained specimens of pancreas were classified according to the age and sex. Simultaneously, the different parts of the pancreas (head, neck, body and tail) were separated. Then each part of the gland was placed in a tray and sectioned transversely. From these slices, small pieces of tissue were taken for histological procedure. Then the tissues were processed and stained with haematoxylin and Eosin (H&E) stain. The slides were examined under microscope in low and high magnification. Number of the Islets per mm2 area and the average transvertical diameter of the Islets of Langerhans were measured with ocular micrometer.Results: The mean number of Islets (per mm2) of the pancreas was 1.91 (SD±0.81) and diameter of Islets of the pancreas was 153.44μm (SD±7.22). The mean number of Islets (per mm2) was 2.05 (SD±0.69); 2.31 (SD±0.96) and 1.38 (SD±0.55) in the age group of 5 to 20 years, 21 to 40 years and years 41 to 64 years respectively (p=0.124). The mean number of Islets (per mm2) was 1.78 (SD±0.71) in male and 2.08 (SD±0.94) in female (p=0.449). The mean diameter of Islets was 151.0 μm (SD±5.9); 156.7 μm (SD±10.3) and 152.7 μm (SD±4.1) in the age group of 5 to 20 years, 21 to 40 years and years 41 to 64 years respectively (p=0.401). The mean diameter of Islets was 158.7μm (SD±5.3) in male and 146.9μm (SD±1.36) in female (p